Stable carbon isotope ratio profiling of illicit testosterone preparations – domestic and international seizures1. Issue 10 (19th August 2014) - Brooker, Lance; Cawley, Adam; Drury, Jason; Edey, Claire; Hasick, Nicole; Goebel, Catrin
<x xml:space="preserve">Abstract</x> Gas chromatography‐combustion‐isotope ratio mass spectrometry (GC‐C‐IRMS) is now established as a robust and mature analytical technique for the doping control of endogenous anabolic androgenic steroids in human sport. It relies on the assumption that the carbon isotope ratios of naturally produced steroids are significantly different to synthetically manufactured testosterone or testosterone prohormones used in commercial medical or dietary supplement products. Recent publications in this journal have highlighted the existence of black market testosterone preparations with carbon isotope ratios within the range reported for endogenous steroids (i.e. δ13C ≥ −25.8 ‰). In this study, we set out to profile domestic and international law enforcement seizures of illicit testosterone products to monitor the prevalence of 'enriched' substrates – which if administered to human subjects would be considered problematic for the use of current GC‐C‐IRMS methodologies for the doping control of testosterone in sport. The distribution of δ13C values for this illicit testosterone sample population (n = 283) ranged from −23.4 ‰ to −32.9 ‰ with mean and median of −28.6 ‰ – comparable to previous work. However, only 13 out of 283 testosterone samples (4.6 %) were found to display δ13C values ≥ −25.8 ‰, confirming that in the vast majority of cases of illicit testosterone administration, current GC‐C‐IRMS doping control procedures would be capable of confirming misuse. Copyright © 2014 John Wiley & Sons, Ltd.